Analysis of nucleophosmin–anaplastic lymphoma kinase (NPM-ALK)-reactive CD8+ T cell responses in children with NPM-ALK+ anaplastic large cell lymphoma. (16th August 2016) - Singh, V K; Werner, S; Hackstein, H; Lennerz, V; Reiter, A; Wölfel, T; Damm-Welk, C; Woessmann, W
Summary: Cellular immune responses against the oncoantigen anaplastic lymphoma kinase (ALK) in patients with ALK-positive anaplastic large cell lymphoma (ALCL) have been detected using peptide-based approaches in individuals preselected for human leucocyte antigen (HLA)-A*02:01. In this study, we aimed to evaluate nucleophosmin (NPM)-ALK-specific CD8 + T cell responses in ALCL patients ensuring endogenous peptide processing of ALK antigens and avoiding HLA preselection. We also examined the HLA class I restriction of ALK-specific CD8 + T cells. Autologous dendritic cells (DCs) transfected with in-vitro -transcribed RNA (IVT-RNA) encoding NPM–ALK were used as antigen-presenting cells for T cell stimulation. Responder T lymphocytes were tested in interferon-gamma enzyme-linked immunospot (ELISPOT) assays with NPM–ALK-transfected autologous DCs as well as CV-1 in Origin with SV40 genes (COS-7) cells co-transfected with genes encoding the patients' HLA class I alleles and with NPM–ALK encoding cDNA to verify responses and define the HLA restrictions of specific T cell responses. NPM–ALK-specific CD8 + T cell responses were detected in three of five ALK-positive ALCL patients tested between 1 and 13 years after diagnosis. The three patients had also maintained anti-ALK antibody responses. No reactivity was detected in samples from five healthy donors. The NPM–ALK-specific CD8 + T cell responses were restricted by HLA-C-alleles (C*06:02 and C*12:02) in all three cases. This approach allowed for the detection of NPM–ALK-reactive T cells, irrespective of the individual HLA status, up to 9 years after ALCL diagnosis. Graphical Abstract: